Technology of organization of competence approach in the context of higher education (Pedagogy of Higher and Secondary Education, 2012)
Bondar L. A. Technology of organization of competence approach in the context of higher education.The conceptual approaches to technology of the organizing student's independent work in the modern university education are substantiated in this article. The different kinds of student’s independent work in the context of the didactic process of the higher education are interpreted in a practical format.
Keywords: technology of the organizing student’s independent work; the formation of professional competencies